Shaker K[+] channel subunits from heteromultimeric channels with novel functional properties. - McCormack, K.; Lin, J.W.; Iverson, L.E.; Rudy, B. (Biochemical and Biophysical Research Communications, 1990)
A large number of related genes (the Sh gene family) encode potassium channel subunits which form voltage-dependent K+ channels by aggregating into homomulitimers. One of these genes, the Shaker gene in Drosophila, generates several products by alternative splicing. These products encode proteins with a constant central region flanked by variable amino and carboxyl domains. Coinjection of two Shaker RNAs with different amino or different carboxyl ends into Xenopus oocytes produces K+ currents that display functional properties distinct from those observed when each RNA is injected separately, indicating the formation of heteromultimeric channels. The analysis of Shaker heteromultimers suggests certain rules regarding the roles of variable amino and carboxyl domains in determining kinetic properties of heteromultimeric channels. Heteromultimers with different amino ends produce currents in which the amino end that produces more inactivation dominates the kinetics. In contrast, heteromultimers with different carboxyl ends recover from inactivation at a rate closer to that observed in homomultimers of the subunit which results in faster recovery. While this and other recent reports demonstrate that closely related Sh family proteins form functional heteromultimers, we show here that two less closely related Sh proteins do not seem to form functional heteromultimeric channels. The data suggest that sites for subunit recognition may be found in sequences within a core region, starting about 130 residues before the first membrane spanning domain of Shaker and ending after the last membrane spanning domain, which are not conserved between Sh Class I and Class III genes.